Male hatchling production in sea turtles from one of the world’s largest marine protected areas, the Chagos Archipelago - Nicole Esteban (Scientific Reports, 2016)
Incubation temperatures at turtle nest depths and implications for hatchling sex ratios of hawksbill turtles (Eretmochelys imbricata) and green turtles (Chelonia mydas) nesting in the Chagos Archipelago, Western Indian Ocean are reported and compared to similar measurements at rookeries in the Atlantic and Caribbean. During 2012-2014, temperature loggers were buried at depths and in beach zones representative of turtle nesting sites in Diego Garcia. Data collected for 12,546 days revealed seasonal and spatial patterns of sand temperature. Depth effects were minimal, perhaps modulated by shade from vegetation. Coolest and warmest temperatures were recorded in the sites heavily shaded in vegetation during the austral winter and in sites partially shaded in vegetation during summer respectively. Overall, sand temperatures were relatively cool during the nesting seasons of both species which would likely produce fairly balanced hatchling sex ratios of 53% and 63% male hatchlings, respectively, for hawksbill and green turtles. This result contrasts with the predominantly high female skew reported for offspring at most rookeries around the globe and highlights how local beach characteristics can drive incubation temperatures. Our evidence suggests that sites characterized by heavy shade associated with intact natural vegetation are likely to provide conditions suitable for male hatchling production in a warming world.